(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In this article, students will be introduced to the English, innovative technologies and teaching through interactive methods and making them interested in learning this language. The opinions and scientific views of scientists and pedagogues regarding the scientific-theoretical aspects of the factors were analyzed and the subjective attitude towards them attitude expressed.